Human capital spending, inequality, and growth in middle-income Asia - Michael R. M. Abrigo; Sang-Hyop Lee; Donghyun Park (Asian Development Bank (ADB), 2017)
Asia's rapid population aging fortifies the case for strengthening human capital investments. Further, the experience of the newly industrialized economies suggests that human capital investments will be a vital ingredient of the transition from middle income to high income. Those investments can also affect equity and public finances. In this paper, we use data from the National Transfer Accounts to empirically analyze the effect of human capital investment in Asian countries on economic growth, inequality, and fiscal balance. Our empirical evidence suggests that human capital investments have a positive effect on labor productivity and, hence, output. The positive effect is stronger for poorer households and, hence, beneficial for equity. We also find that such investments can generate sufficient tax revenues to improve the fiscal balance. Overall, our evidence points to a positive effect of human capital on growth, equity, and fiscal balance in Asia.
Keywords: J24; H52; I24; I25; 330; Asia; fiscal balance; growth; human capital; inequality